PROXIMATE COMPOSITION OF COMPOSITE CAKES FORTIFIED WITH COCOYAM, PLANTAIN, AND BAMBARA NUT FLOUR BLENDS FOR ADOLESCENTS - Kanayo Agidi, Eunice; Oritsegbubemi Arubayi, Diana; Ego Azonuche, Juliana (Barkah Publishing, 2025)
Adolescents require nutrient-dense foods to support their rapid growth and cognitive development, yet many snacks consumed by this age group are high in calories but low in essential nutrients. Cake, a popular and convenient snack, can serve as a medium for nutrient fortification using locally available crops. The study adopted an experimental design conducted at Delta State University, Abraka, to develop and evaluate cakes produced from wheat and composite flours of cocoyam, plantain, and bambara nut in varying proportions. Fifteen purposively selected panelists assessed the cakes’ nutritional, sensory, and shelf-life qualities using validated and reliable instruments, with reliability coefficients of 0.81 and 0.88. Standard methods (AOAC, 2010–2015) were used to determine moisture, protein, fat, ash, fiber, carbohydrate, and vitamin A contents. Cakes were prepared under controlled laboratory conditions following standardized baking procedures. Data were analyzed using mean, standard deviation, ANOVA, and Duncan Multiple Range Test at a 0.05 significance level. The results showed that 40% of the sensory panelists were male and 60% female, with 53.33% undergraduates and 46.67% postgraduates. Proximate analysis revealed variations in nutrient composition among cakes fortified with cocoyam, plantain, and bambara nut. Moisture ranged from 20.94% to 24.46%, protein from 7.33% to 9.65%, fat from 22.25% to 27.68%, fiber from 0.57% to 1.44%, ash from 1.10% to 2.61%, and carbohydrate from 35.60% to 46.76%. ANOVA indicated significant differences (P≤0.05) in moisture, protein, fat, fiber, and ash contents among samples, except for carbohydrates, which showed no significant difference (P≥0.05). Composite cakes improved protein and mineral contents compared to 100% wheat cake. The study concludes that composite cakes enriched with cocoyam, plantain, and bambara nut flours are nutritionally superior and well-accepted alternatives to 100% wheat cakes. Their adoption can promote healthier snacking options among adolescents, enhance dietary diversity, and reduce reliance on imported wheat flour.